Inovasi Produk Tahu Gurilem Cipatat Berdasarkan Keinginan dan Kebutuhan Konsumen Menggunakan Quality Function Deployment - Puspita, Neng; Retno Prasinta, Widya (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in supporting the national economy, particularly in the food processing sector such as tofu production. Tahu Gurilem Cipatat, a local tofu producer in West Bandung Regency, faces challenges in meeting consumer demands amid increasing competition. Therefore, product innovation is essential to ensure business sustainability. This study aims to identify consumer needs and preferences for tofu products and translate them into technical specifications using the Quality function deployment (QFD) method. The research uses a descriptive quantitative approach with data collected through questionnaires, observations, and interviews. The population consists of housewives in Cipatat Village, with 70 respondents selected using the Slovin formula. Data analysis is conducted through the QFD method by constructing a House of quality (HoQ), which links customer requirements (WHATs) with technical characteristics (HOWs), . Based on the results of the study, the selected product innovation resulting from the Quality function deployment (QFD) analysis includes a balanced taste, fresh and timely products, easy consumer access, appropriate portion sizes, and affordable prices.